Combined Effects of Resveratrol and Vitamin E From Peanut Seeds and Sprouts on Colorectal Cancer Cells - Chunfeng Wang; Chunfeng Wang; Na Wang; Na Wang; Na Wang; Na Li; Qiuying Yu; Qiuying Yu; Fangyu Wang (Frontiers Media S.A., 2021)
Resveratrol (RES) and Vitamin E (VE) are anti-cancer active ingredients with relatively high content in peanut seeds and sprouts. This study aimed to determine the synergistic inhibitory effect of RES and VE on colorectal cancer. Using 5-FU as a positive drug control, the effect of RES combined with VE on HCT-8 cells was determined, and cell viability was detected using the cell-counting kit 8 (CCK8) method. Cell morphology changes were observed using optical microscopy. Cell migration ability was evaluated by the scratch test, while cell colonies were determined by the cloning test formation ability. Apoptosis status was assessed by flow cytometry and nuclear staining by DAPI, and the expression level of apoptosis-related proteins was determined by western blotting. Compared with the single component group, the RES combined with VE group significantly inhibited the growth and proliferation of HCT-8 intestinal cancer cells in vitro. The RES combined with VE group had a greater impact on cell morphology changes and cell colony formation and significantly reduced cell migration ability and intestinal cancer cell apoptosis (p < 0.05). Additionally, combined treatment with RES and VE significantly upregulated the expression of pro-apoptotic proteins BAX, caspase-3, caspase-8, and caspase-9, and downregulated the expression of anti-apoptotic protein BCL-2, compared to the single component treatment. RES combined with VE is effective in promoting intestinal cancer cell apoptosis. This study demonstrated the significant positive synergy of RES and VE on HCT-8 cells, providing a new perspective for more effective use of RES.